Austria : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2004)
Austria's 2004 Article IV Consultation reports that the economy has continued to perform relatively well, unemployment is among the lowest in the European Union, and competitiveness remains strong. Also, a gradual recovery is under way and short-term economic prospects are positive, although risks remain. There are areas of potential risk stemming primarily from exposure of Austrian banks in central and eastern European countries and foreign currency loans to households; and there is scope for strengthening supervision and reviewing the current deposit insurance system over the medium term.